Improved stability in organic light‐emitting devices by mixing ambipolar and wide energy gap hosts. Issue 7 (21st March 2019) - Bangsund, John S.; Hershey, Kyle W.; Rathwell, Dominea C. K.; Na, Hong‐Yeop; Jeon, Jeong‐Hwan; Trefonas, Peter; Holmes, Russell J.
Abstract: We demonstrate improved stability in phosphorescent organic light‐emitting devices (OLEDs) by incorporating a wide energy gap host material into an ambipolar emissive layer. Unlike conventional mixed‐host OLEDs that combine hole‐ and electron‐transporting hosts, charge transport in this device occurs primarily along the ambipolar host and the emitter, while the wide energy gap host serves to modify the charge injection and transport characteristics of the emissive layer. This approach allows both the width and position of the exciton recombination zone to be tuned without introducing exciplex states. Whereas overall device stability improves with increasing recombination zone width in conventional mixed‐host OLEDs, mixing in this system reduces the recombination zone extent yet still increases device lifetime. By decoupling luminance losses into the photostability of the emitter and the exciton formation efficiency, we show that this enhancement arises from a trade‐off between bulk and interfacial degradation. The addition of the wide energy gap host moves the recombination zone away from the interface between the hole‐transport layer and the emissive layer, sacrificing a modest increase in bulk degradation to substantially reduce interfacial degradation. We find that the lifetime can be improved by 50% by balancing these competing degradation pathways. Abstract : Device stability is optimized by managing the exciton recombination zone to limit interfacial degradation in phosphorescent OLEDs. A trade‐off is observed between the width and position of the recombination zone. These parameters are shown to be tunable in an unconventional cohost system by mixing ambipolar and wide energy gap hosts.